Opera Occulta (Res Medica, 2013)
This simple people [ChaymaIndians] have an insuperable dislike to cohabit with any deformed woman. This is indeed common to most savage tribes in a state of Nature, which is a state of great equality. Unless a woman be well formed she is neglected and dies barren.In Europe and wherever artificial manners prevail, ugly and even deformed women marry. The cupid of commercial countries is not the cupid of Pastoral poets. . . . He speaks too of a gentleman begetting a daughter with eyes and hair differently coloured from any of his children, his wife, or himself, and imagining this arose from his thinking (sub coitu) on a little brunette he had taken a fancy to. It might or might not be from this cause, but I have no idea that hanging the bridal bedwith a pall, would tend in the least to produce a Negro child. The sight of a Negro footman might be added without danger; but their contact would be more effectual in changing the colour of a first born. Physiognomy is no doubt varied by causes operational on the mind at or about the time of conception or it may be on the senses, and it is between the Physiognomy of man in its varieties and the variety of colour in domesticated animals that the analogy seems chiefly to exist.